SGLT2-Inhibitors - significant role in Heart Failure treatment - Wielgus, Karol; Bator, Piotr; Pawłowska, Maria; Magiera, Karol; Rachwał, Krystian; Antos, Maria; Ramian, Jan; Łyko, Grzegorz (Journal of Education, Health and Sport, 2024)
Heart failure (HF), which has a high morbidity and mortality rate, is nevertheless a common and crippling ailment, especially in older populations. The complicated pathophysiology of heart failure (HF), which includes oxidative stress, endothelial dysfunction, fibrosis, and inflammation, is frequently not sufficiently treated despite advances in medication. Inhibitors of the sodium-glucose co-transporter 2 (SGLT2) have become a key treatment for HF in patients with varying left ventricular ejection fractions (LVEF). SGLT2 inhibitors have been shown in recent clinical trials to considerably lower hospitalization rates for heart failure, cardiovascular mortality, and all-cause mortality. The mechanisms of SGLT2 inhibitors, such as better ventricular loading, increased heart metabolic efficiency, and decreased inflammation and necrosis, are covered in this review. Additionally, we provide an overview of four important clinical trials—DAPA-HF, EMPEROR-Reduced, EMPEROR-Preserved, and DELIVER—highlighting their effectiveness in lowering unfavourable cardiovascular outcomes for patients with heart failure who have preserved (HFpEF), slightly reduced (HFmrEF), or reduced (HFrEF). The results validate the need for SGLT2 inhibitors in all-inclusive HF treatment plans by highlighting their adaptability and safety in a range of clinical contexts.